Unlocking Chemically Encrypted Information Using Three Types of External Stimuli - Zhang, Hanwei; Li, Qingyun; Yang, Yabi; Ji, Xiaofan; Sessler, Jonathan L (Journal of the American Chemical Society, 2021)
Encryption is critical to information security; however, existing chemical-based information encryption strategies are still in their infancy. We report here a new approach to chemical encryption involving a supramolecular gel QR (quick response) code with multiple encryption functions. Three color “turn-on” supramolecular polymer gels, G1–G3, were prepared that produce pink, purple, and yellow colors when subject to treatment with acetic acid vapor, UV light, and methanolic FeCl3, respectively. As the result of hydrogen-bonding interactions at the gel interfaces, the three gels can be assembled to produce gel G4. Engraving a QR code pattern onto G4 then gave gel G5. When one or two stimuli are applied to the individual pieces corresponding to the QR engraved versions of the gels G1–G3 making up G5, a complete scannable pattern is not displayed, and the stored information cannot be recognized. Only when three different stimuli are applied at the same time does G5 give a complete recognizable pattern allowing the stored information to be retrieved. This strategy was applied to the decryption-based opening of a coded lock.